2015
DOI: 10.1007/s00345-015-1562-z
|View full text |Cite
|
Sign up to set email alerts
|

Is vaginal mucosal graft the excellent substitute material for urethral reconstruction in female-to-male transsexuals?

Abstract: With prefabrication of vaginal mucosal graft, we reconstruct a competent phallic neourethra in these FTM transsexuals. According to its histological similarities and source character, the vaginal mucosa is the excellent substitute material for promising urethral reconstruction in FTM transsexuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
0
31
0
2
Order By: Relevance
“…While prelamination has predominantly been performed with skin grafting, mucosal grafts allow for greater homology between native urethra and the constructed components. Histologically, mucosa has nonkeratinized epithelium and therefore has greater similarity to the urethra than skin, which has a keratinized epithelium [ 5 , 8 ]. There is also a greater chance of successful wound healing with mucosa, leading to less scar contracture at the recipient site [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While prelamination has predominantly been performed with skin grafting, mucosal grafts allow for greater homology between native urethra and the constructed components. Histologically, mucosa has nonkeratinized epithelium and therefore has greater similarity to the urethra than skin, which has a keratinized epithelium [ 5 , 8 ]. There is also a greater chance of successful wound healing with mucosa, leading to less scar contracture at the recipient site [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Buccal mucosa is commonly used for reconstructive urethroplasty because it is hairless, accustomed to a wet environment, and easy to harvest and it has a thick epithelium [ 4 ]. Thus, vaginal mucosa, which possesses properties similar to buccal mucosa, is often used to construct the pars fixa in the FtM patient [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to anecdotal reports of urinary leakage and chronic accumulation in the vaginectomy cavity, which can require complex, secondary correction, some centers opt to perform vaginectomy at the time of hysterectomy and salpingo-oophorectomy [17,18] . Still, many high-volume centers prefer to perform vaginectomy at the time of pars fixa construction to allow the use of vascularized anterior vaginal myomucosal flaps to create a portion of the pars fixa urethra, hypothesizing that this may reduce the incidence of urinary strictures and fistulas [15,[19][20][21] . Note that although pars fixa construction has been described in patients who choose not to undergo vaginectomy, the significant risk profile for urethral complications with this approach leads most centers, current authors included, to advise against it.…”
Section: Hysterectomy Salpingo-oophorectomy Vaginectomymentioning
confidence: 99%
“…9 Furthermore, grafting techniques, whether using vaginal or buccal mucosa, also have a low urethral stricture rate, at 4.5% and 0%, respectively. 15,16 Much knowledge regarding urethral stricture is based on reports by Lumen et al 17,18 Their original papers indicated that the urethral anastomosis site is the most common location for stricture. Other indicated sites were the meatus, phallic urethra, fixed part urethra, and combined complex strictures, in descending order of incidence.…”
Section: Urethral Stricturementioning
confidence: 99%